The Urban Poor in Latin America - Fay, Marianne (Washington, DC: World Bank, 2012)
With three quarters of its population living in cities, Latin America is now essentially an urban region. Higher urbanization is usually associated with a number of positives, such as higher income, greater access to services, and lower poverty incidence, and, Latin America is no exception. Today, urban poverty incidence, at 28 percent, is half that of in rural areas; extreme poverty, at 12 percent, is a third. Despite this relatively low poverty incidence, the absolute number of poor people is high, and most studies agree that about half of Latin America's poor live in urban areas. The Bank's own estimates suggest that 60 percent of the poor (113 million people) and half the extreme poor (46 million individuals) live in urban areas. The report reviews what is specifically urban about poor people living in cities, which reveals a number of facts, critical to understanding the challenges facing the urban poor, and the means to address these challenges. Three preconceived ideas are discussed, that tend to cloud judgment about urban poverty. All three spring from the common misperception that urban statistics are representative of the urban poor. However, the relatively low incidence of poverty in cities, combined with Latin America's high inequality, imply urban statistics are almost never representative of the urban poor. Concerning the differences between urban and rural poor, the need for differentiated strategies to tackle urban as opposed to rural poverty is implied, and, the first and most important differential is the greater integration of the urban poor into the market economy. Second, while urban areas are not systematically unequal than rural areas - it depends on the country, and, within countries, on the city - they are much more heterogeneous socio-economically, or with respect to economic activities and processes. Third, heterogeneity notwithstanding, Latin American cities tend to be highly segregated. As a result, social exclusion coexists with (relative) physical proximity to wealth, services and opportunities. This gives rise to negative externalities, or neighborhood effects that result in a lower ability to access jobs, lower earnings, and lower educational achievements. Fourth, social networks are less stable in urban areas, with relationships based more on the quality of reciprocal links between individuals and friends, than on familial obligations. Fifth, urban living also means much greater exposure to organized crime, drugs and gang violence. This is true for the population as a whole, but it has particularly dismal implications for the poor living in the slums of Latin America's large cities, where drug-traffic is now pervasive. Finally, another important characteristic of urban poverty has to do with overwhelmed, rather than absent services. The underlying hypothesis of this report is that, indeed, the causes of poverty, the nature of deprivation, and the policy levers to fight poverty are, to a large extent, site specific.